What Do We Remember? : Identities, Memories and Central European History - Lanska, John R. (My University, 2015)
The goal of this project was to transform the course HIST 325 "History and Memory in Central Europe" from an online, three-week course into a full-semester honors course that aligned with the newly-adopted Liberal Education global and integrated outcomes and rubrics.
Color poster with text and photographs.
Keywords: Cultural memory; Immigration; Central European history; Posters